(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
This research sought to explore factors that influence job search behaviour of atypical workers at a manufacturing firm in Zimbabwe. Twelve employees who participated in this study were selected using purposive sampling technique. Semi- structured interviews were used to collect data from research participant. The researchers thematically analysed the collected using ATLAS.ti system. The study found that job search behaviours of atypical workers at the manufacturing firm in Zimbabwe are influenced by a number of factors. The four main factors that influence workers’ job search behaviours identified by research participants are type of employment contract, wage rate, macro-economic and labour market conditions and educational and professional qualifications. Only a few research participants indicated that the desire for a good work-life balance also influences job search behaviour of workers. The current study recommends that organisations should make an effort to know factors that influence atypical workers’ job search behaviour. This study also urges supervisors at the case organization to improve contractual terms of atypical workers to reduce workers’ propensity to look for new jobs.